URGENSI NASIKH-MANSUKH DALAM LEGISLASI HUKUM ISLAM - Noor Rohman Fauzan (Faculty of Sharia and Law UNISNU Jepara, 2014)
Nasikh-mansukh needs to be a concern in this paper that is approximately designed to find two things: first, the true concept of naskh-mansukh itself; second, regarding its application to dinamic Islamic law. The limits resemblance that appears between naskh and takhsish concepts can be known through their differences. The most striking difference is the existence of two texts in naskh; nash nasikh and nash mansukh time of which are inconcurrent. It means that nash nasikh (abrogator ) came after nash mansukh (abrogated). While in takhsish, the specifying texts (mukhashshish) is concurrent time with the specified texts (mukhashshash)). From the discussion of naskh arise two dominant opinions among Muslims: (1) the opinion that accepts the existence of naskh and (2) the opinion that rejects the existence of naskh.Because of the absence of the hadeeth sahih that can be considered as texts qath'iy in explaining which verses are mansukhah (abrogated), then it is necessary to further examine this issue of naskh especially if associated with the development of Islamic law issues that are increasingly complex.nasikh-mansukh, al-qur??an, hadis, legislation, islamic law.Persoalan nasikh-mansukh perlu menjadi perhatian dalam tulisan ini yang kurang-lebihnya dirancang untuk menemukan dua hal: pertama, kesejatian konsepsi nasikh-mansukh itu sendiri, kedua, mengenai penerapannya dalam hukum Islam yang dinamis. Pengertian naskh dan takhsish yang di antara keduanya ada tasyabbuh dapat diketahui batas-batasnya dengan melihat perbedan-perbedaanya. Perbedaan yang paling mencolok ialah di dalam naskh terdapat dua nash; nash nasikhdan nash mansukh yang tidak berbarengan waktunya, artinya nash nasikh datang sesudah nash mansukh. Sedangkan di dalam takhsish, nash yang men-takhshish (mukhashshish) berbarengan waktunya dengan nash yang di-takhshish. Dari pembahasan naskh timbul dua pendapat yang dominan di kalangan ummat Islam: (1) pendapat yang menerima adanya naskh dan (2) pendapat yang menolak adanya naskh. Karena tidak adanya hadits shahih yang dapat dianggap sebagai nash qath'iy dalam menjelaskan ayat-ayat mana yang mansukhah, maka sangat diperlukan upaya untuk mengkaji lebih jauh permasalahan naskh ini terutama jika dikaitkan dengan perkembangan persoalan hukum Islam yang semakin kompleks.